Práticas pedagógicas mediatizadas pelas tecnologias digitais da informação e comunicação em tempos de pandemia da COVID-19 - Souza, Beatriz dos Santos (2023)
This research aimed to analyze the state of knowledge of pedagogical practices mediated by Digital Information and Communication Technologies (ICTs) and evidenced in the scientific production that addresses basic education in the context of the COVID-19 pandemic. Being a qualitative, exploratory and bibliographic investigation, it was carried out a Systematic Literature Review (SLR) which considered articles produced in the years 2020 and 2021. The search sources were CAPES Journal Portal, the Education Resources Information Center (ERIC) and the Scientific Open Access Repositories of Portugal (RCAAP). After applying the previously defined inclusion and exclusion criteria, a corpus of 34 articles written either in Portuguese or in English was selected and submitted to the stages of content analysis, with the support of the NVivo 12 software. Through the inductive process of analysis, the following categories emerged: 1) pedagogical practices; 2) resources, platforms and tools; 3) challenges; 4) interpersonal interactions (student-teacher, student-student and family participation); 5) engagement; 6) assessment; 7) curriculum; 8) teacher training; 9) technology; 10) future prospects. The approach analysis of each category in the articles allowed us to visualize the practices and their results for student learning, providing a wide range of examples that indicate the reframing of education during the pandemic, as well as indications of future changes